First International Conference on Optical Communications and Networks (ICOCN 2002) : Shangri-La Hotel, Singapore, 11-14 November 2002 - Omidyar, Cambyse Guy, 1944-; Ghafouri-Shiraz, H.; Zhong, W. D. (Wen De) (World Scientific, 2002)
The proceedings of the First International Conference on Optical Communications and Networks present high quality recent research results in the areas of optical communications, network components, architectures, protocols, planning, design, management and operation.